Implementation of the Erp (Enterprise Resource Planning) Program in Oil Palm Plantation Data Processing - In Chien; Daniel Firmanto Meliala; Anita Christine Sembiring (Institute of Computer Science (IOCS), 2022)
In all activities in oil palm plantation offices, we often find problems regarding the distance between offices and gardens which are very far away, even the distance between the gardens and offices is between islands, so we need a computer operational system program to reach all the data needed for processing a data into a financial reports and work progress of a job.Many people do not know about the program that is used to connect one part to another so that in data processing and monitoring the progress of a job it becomes hampered or the resulting data is incomplete or invalid for use because the authenticity of the data produced is dubious or vulnerable. to be manipulated by various parties, so with a program that can reach all of them, it can increase the efficiency of data processing and can be processed and produce accurate data for the company to need in the continuity of the company.